Peran Dinas Sosial dalam Penanganan Lanjut Usia Terlantar di Kabupaten Pohuwato - Fauzan Atjil; Gretty Syatriani Saleh (Universitas Islam Darul Ulum Lamongan, 2025)
This research aims to analyze the role of the Social Services Office of Pohuwato Regency in handling neglected elderly individuals. Neglected elderly are a vulnerable group facing various physical, health, social, and economic problems, often due to the absence of family, economic limitations, or poor family relationships. This study uses a qualitative approach focusing on the facilitative, educational, representational, and technical roles of the Social Services Office. The research findings indicate that the Social Services Office of Pohuwato Regency plays an active role in providing shelter, facilitating basic needs, offering education, advocacy, and managing data to ensure the well-being of neglected elderly. This role is crucial in fulfilling the basic rights and improving the quality of life for neglected elderly in the region.